Di’ao Xinxuekang Capsule, a Chinese Medicinal Product, Decreases Serum Lipids Levels in High-Fat Diet-Fed ApoE–/– Mice by Downregulating PCSK9 - Qu, Liping; Li, Didi; Gao, Xiaoping; Li, Yongwei; Wu, Jianming; Zou, Wenjun (Frontiers in Pharmacology, 2018)
Numerous risk factors are responsible for the development of atherosclerosis, for which an increased serum level of low-density lipoprotein cholesterol (LDL-C) is a driving force. By binding the low-density lipoprotein cholesterol receptor (LDLR) and inducing LDLR degradation, proprotein convertase subtilisin/kexin type 9 (PCSK9) plays a key role in cholesterol homeostasis regulation. The inducing of PCSK9 expression is also as an important reason for statin intolerance. The Di’ao Xinxuekang (DXXK) capsule extracted from Dioscorea nipponica Makino is a well-known traditional Chinese herbal medicine product used in atherosclerotic cardiovascular disease. Although DXXK has been widely used in atherosclerotic cardiovascular treatment for nearly 30 years, studies on the potential mechanisms of the lipid-lowering effect are very limited. The purpose of the present study was to demonstrate the possible involvement of the PCSK9/LDLR signaling pathway in the lipid-lowering and anti-atherosclerotic effect of DXXK in high-fat diet-fed ApoE-/- mice. The results showed that DXXK treatment alleviated hyperlipidemia, fat accumulation and atherosclerosis formation in ApoE-/- mice. Furthermore, changes in the expression of PCSK9 mRNA in liver tissue and the circulating PCSK9 level in ApoE-/- mice were both reversed after DXXK treatment, and upregulation of LDLR in the liver was also detected at the protein level in DXXK-treated mice. Our study is the first to show that DXXK could alleviate lipid disorder and ameliorate atherosclerosis with downregulation of the PCSK9 in high-fat diet-fed ApoE-/- mice, suggesting that DXXK may be a potential novel therapeutic and may support statin action in the treatment of atherosclerosis.